(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Tatyana I. Pavlova (Rostov-on-Don, Russian Federation) The quality of written speech of bilingual students is determined by the specific features of spelling phenomena, the development of their speechthinking abilities, the influence of interference, and the creation of conditions for its improvement. The formation of spelling literacy requires various types of exercises. The learning process becomes effective if the system of exercises is complex, providing the full formation of spelling skills and abilities on the speech basis. Key words: bilinguals, spelling, written speech, principles of spelling, typology of exercises, speech development. DOI 10.23683/1995-0640-2019-2-174-179